Pengaruh Edukasi Kesehatan dalam Meningkatkan Pengetahuan Siswa Tentang Anemia di SMA 2 Tanah Jambo Aye Kecamatan Tanah Jambo Aye Kabupaten Aceh Utara - Futry Maysura; Nazalia Nazalia (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Anemia is a significant community health problem, especially among young females, including students. Females have a high risk of anemia occurrence among students. Education regarding anemia was necessary to provide more knowledge to students. This situation has serious implications for an individual’s physical and mental health and the quality of life. The study aims to assess the role of nutrition education in the prevention of anemia as well as the relationship of knowledge-level toward anemia for students. Data were collected through questionnaires distributed before and after information was disseminated to 20 respondents aged 15-17 years. The results of this analysis before counseling showed that most students understood enough(62%) about anemia . This education comprised definition, causes, symptoms, effects and preventive aspects of anemia. This study indicates that nutrition education is effective in improving the knowledge of students in an school(100%). The detailed knowledge of vital aspects regarding anemia after the education is delivered is envisaged to foster better behavioral changes near this health problem. It also highlights the need for educational intervention to raise awareness among public health students towards various aspects of anemia.